A commitment to care: residential child care work in England - Amanda Mainey (Scottish Journal of Residential Child Care)
Residential child care is a valuable and complex job. It requires a wide range of skills, and can make a huge difference to the lives of some of our most vulnerable young people. So why are there high levels of vacancies and staff turnover in residential child care homes across England? Why does the view persist that residential child care is the 'Cinderella' of social care work?